2022
DOI: 10.1093/advances/nmab149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microbiota-Driven Therapy on Circulating Indoxyl Sulfate and P-Cresyl Sulfate in Patients with Chronic Kidney Disease: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Indoxyl sulfate (IS) and p-cresyl sulfate (PCS), protein-bound uremic toxins, exacerbate the deterioration of renal function and increase the risk of cardiovascular events in chronic kidney disease (CKD) patients. The effects of microbiota-driven therapy (probiotics, prebiotics or synbiotics) on decreasing circulating IS and PCS concentrations are controversial; thus, we performed the present systematic review and meta-analysis to assess the effects of microbiota-driven therapy on the circulating IS and PCS co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…This translated to a reduction in most commonly studied gut-derived uremic toxins, and we postulate that effect was the main driver of the positive effects on bone and vascular calcification. Two meta analyses of prebiotic, probiotic, and synbiotic therapies identified conflicting results on whether these interventions lowered indoxyl sulfate, but both studies (similar to our study) reported decreased p-cresol sulfate levels with interventions 58, 59 . Indoxyl sulfate is a ligand for the aryl hydrocarbon receptor (AhR) that is critical in the removal of both environmental and endogenous toxins 60 .…”
Section: Discussionsupporting
confidence: 56%
“…This translated to a reduction in most commonly studied gut-derived uremic toxins, and we postulate that effect was the main driver of the positive effects on bone and vascular calcification. Two meta analyses of prebiotic, probiotic, and synbiotic therapies identified conflicting results on whether these interventions lowered indoxyl sulfate, but both studies (similar to our study) reported decreased p-cresol sulfate levels with interventions 58, 59 . Indoxyl sulfate is a ligand for the aryl hydrocarbon receptor (AhR) that is critical in the removal of both environmental and endogenous toxins 60 .…”
Section: Discussionsupporting
confidence: 56%
“…Change in gut microbes was investigated using prebiotic, probiotic, or symbiotic, however; the resulting data are unsettled. 31,32…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of the intestinal microbiota in AVF‐induced exacerbation of uremia, therapies such as prebiotics and synbiotics may deserve further investigations, with early evidence demonstrating that these may reduce the levels of p‐cresyl sulfate in patients with CKD. 71 …”
Section: Discussionmentioning
confidence: 99%